Pengaruh Bea Perolehan Hak Atas Tanah dan Bangunan, Pajak Bumi dan Bangunan, dan Retribusi Daerah terhadap Pendapatan Asli Daerah Yogyakarta - Laurensius Fernando; Uum Helmina Chaerunisak (Jurnal Literasi Akuntansi, 2025)
Purpose: Determining the impact of regional levies, land and building taxes, and fees for obtaining land and building rights on Yogyakarta's initial regional income is the goal of the study. Method: This kind of study falls under the category of quantitative research. The financial reports of the Yogyakarta Special Region Government Regional Civil Service Agency, which were released between 2010 and 2022, serve as the sample for this study. Financial reports from Yogyakarta, which were released between 2010 and 2022, serve as the secondary data source for this information. Tiered linear regression analysis is the method used for data analysis. Finding: The study's findings indicate that Regional Levy has a major impact on Yogyakarta's Original Regional Income (PAD), Land and Building Tax (PBB) revenue has a positive and significant impact on Yogyakarta's PAD, and the BPHTB tax has no effect on PAD. Novelty: This study offers novelty by simultaneously examining the effects of BPHTB, PBB, and regional retribution on Yogyakarta’s local revenue (PAD), providing a comprehensive analysis rarely found in previous research that typically focuses on these variables separatel